Development of tools to study personal weight control strategies: OxFAB taxonomy. - Hartmann-Boyce, J; Aveyard, P; Koshiaris, C; Jebb, S (Wiley, 2016)
To describe the development of the Oxford Food and Activity Behaviors (OxFAB) taxonomy and questionnaire to explore the cognitive and behavioral strategies used by individuals during weight management attempts.The taxonomy was constructed through a qualitative analysis of existing resources and a review of existing behavior change taxonomies and theories. The taxonomy was translated into a questionnaire to identify strategies used by individuals. Think-aloud interviews were conducted to test the face/concept validity of the questionnaire, and test-retest reliability was assessed in a sample of 138 participants.The OxFAB taxonomy consists of 117 strategies grouped into 23 domains. Compared to taxonomies used to describe interventions, around half of the domains and strategies identified are unique to the OxFAB taxonomy. The OxFAB questionnaire consists of 117 questions, one for each strategy from the taxonomy. Test-retest resulted in a mean PABAK score of 0.61 (SD 0.15). Questions were revised where appropriate.The OxFAB taxonomy and questionnaire provide a conceptual framework to identify the cognitive and behavioral strategies used by individuals during attempts at weight control.